2021
DOI: 10.3390/ijerph18020514
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Adults with Cardiovascular or Metabolic Diseases by Gender

Abstract: This study aimed to compare mental health in people with cardiovascular or metabolic diseases and the general adult population in each gender. Cardiovascular and metabolic diseases affect mental health, and the prognosis and incidence rates of these diseases differ by age. To date, studies comparing mental health in adults with cardiovascular or metabolic diseases by gender and with the general population have been insufficient. This work is a cross-sectional study. Data from 9828 men and 13,389 women aged 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…13 These dissonant findings could be partially explained by the presence of high cardiovascular risk conditions, which have been associated with worse mental health outcomes. 26 Moreover, it is important to consider that our data were collected during or after the most severe period of the COVID-19 pandemic, when mental health issues appeared as a concurrent epidemic. 43 In fact, studies have shown that the pandemic had important repercussions on SLE patients’ psychological state, with high levels of stress, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These dissonant findings could be partially explained by the presence of high cardiovascular risk conditions, which have been associated with worse mental health outcomes. 26 Moreover, it is important to consider that our data were collected during or after the most severe period of the COVID-19 pandemic, when mental health issues appeared as a concurrent epidemic. 43 In fact, studies have shown that the pandemic had important repercussions on SLE patients’ psychological state, with high levels of stress, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This may explain, along with disease-specific factors (e.g., disease activity and duration), 21 the 5–6-fold increase in risk for cardiovascular diseases observed in SLE. 22 It is important to highlight that cardiovascular risk factors and diseases are associated with worse HRQL, 23,24 fatigue, 25 mental health, 26,27 and sleep quality. 28,29 Interestingly, the impact of cardiovascular risk factors on some of these health outcomes seems to be interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Depression occurs in one in five patients with coronary artery disease, peripheral artery disease, or heart failure (12). Men or women with CVDs are at high risk of stress, depression, and suicidal ideation (13). Some current research indicates that patients with heart failure are more likely to have ongoing anxiety during hospitalization and poor quality of life (14,15).…”
Section: Introductionmentioning
confidence: 99%